Window-of-opportunity trials to screen effective agents and optimize dose in breast cancer prevention - G. Aurilio; D. Serrano; M. Lazzeroni; A. Guerrieri-Gonzaga; H. Johansson; S. Gandini; I. M. Briata; M. D’Amico; S. Spinaci; P. Veronesi; V. Galimberti; M. Intra; et al. (npj Breast Cancer)
Abstract Window-of-opportunity trials are a path to screen effective agents and optimize dose in breast cancer risk reduction. We review the scientific evidence regarding the utility of window-of-opportunity trials to screen effective agents and optimize dose for successful risk reduction/interception of breast cancer. Low-dose tamoxifen was evaluated in a window-of-opportunity trial and then validated in a phase-III trial. We are now studying similar activity with low-dose exemestane.